Kinerja Keuangan Sebagai Determinan Implementasi Blue Accounting Disclosure pada Perusahaan Maritim, Energi, dan Pertambangan di Indonesia - Ester Sabatini; Vivian Angelina Soegiharto Wibowo (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2026)
Environmental degradation within the maritime, energy, and mining sectors requires a transformation toward sustainable corporate reporting through blue accounting disclosure (BAD). However, this voluntary mechanism is often constrained by internal financial trade-offs. This study aims to empirically examine the influence of financial performance projected through profitability (ROA), liquidity (CR), and leverage (DER) on BAD. Employing a quantitative approach with purposive sampling, data were gathered from maritime, energy, and mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2025. The data were analyzed using multiple linear regression with a Random Effect Model (REM). The results indicate that profitability has a negative but insignificant effect on BAD. Conversely, both liquidity and leverage exert a significant negative impact on BAD. This confirms that highly liquid firms reduce voluntary disclosure for operational efficiency under Legitimacy Theory, while heavily indebted firms prioritize credit obligations over blue accounting costs under Agency Theory. This research contributes to sustainability literature by identifying internal financial constraints in developing markets and urges regulators to implement mandatory reporting frameworks.